Perbedaan Tingkat Depresi Antara Lansia Yang Tinggal Di Panti Wredha Dharma Bhakti Dan Yang Bersama Keluarga Di Kelurahan Pajang - Monika, Anggun Dewi, dr. Rh. Budhi Muljanto, Sp. KJ, dr. Dodik Nursanto (2014)
Background : The population of elderly had increased. Indonesia occupied on fifth place in the world as the largest elderly population. The impact from increasing the number of population in 2020, Indonesia will be facing health problem related to depression as the main problem. Commonly elderly lives with family but there are elderly who lives in elderly nursing house. The aim of this research is to known the differences of depression level between elderly who lives in Dharma Bhakti Nursing House and who lives with family in Pajang. Method : This research is the kind of observational analytic research, with cross sectional approach. The data had taken by simple random sampling with 31 sample of elderly who lives in elderly nursing house and 31 samples of elderly who lives with family. This research used analysis test that is unpaired t test. Result : The differences data between depression level between elderly who lives in Dharma Bhakti Nursing House and who lives with family in Pajang tested with unpaired t test, with p <0,01 means that very had a meaning in statistic. Conclusion : There were significant differences between the rates of depression in elderly who lives in Dharma Bhakti Nursing House and who lives with family in pajang.